What Is the Most Cost-Effective Breeding Program for Dairy Heifers—Timed AI, Estrous Detection, or a Combination of Both? - Klibs N. Galvão; Eduardo S. Ribeiro; Jose Eduardo P. Santos (EDIS)
As any other business enterprise, the sustainability of a dairy farm is highly dependent on economics. In order to obtain a profitable return on assets, there is a constant need to maximize outputs and, oftentimes, to minimize inputs. Reproduction influences both milk production and number of replacement heifers available on a farm; therefore, reproductive efficiency becomes a key determinant of dairy cow profitability. This 3-page fact sheet presents information from recently published work that looked at the economics of different reproductive programs for breeding heifers that use timed AI only, estrus detection only, or a combination of both. Written by Klibs N. Galvão, Eduardo S. Ribeiro, and Jose Eduardo P. Santos, and published by the UF Department of Veterinary Medicine-Large Animal Clinical Sciences, May 2014.